STUDY THE BEHAVIOR OF ASPHALT MIX AND THEIR PROPERTIES IN PRESENCE OF NANO MATERIALS - Patidar, Aman; Sarkar, Dipankar; Pal, Manish (MATTER: International Journal of Science and Technology, 2018)
The rapid increase in the traffic load, higher traffic volume, daily and seasonal variation in temperature led to pavement distresses like rutting, fatigue and thermal cracking etc. because of this pavement fails during service life so that bitumen needs to be modified with some additive. In this study VG30 grade bitumen modify with addition of nanosilica with 1% to 5% (increment of 1%) by weight of bitumen. Hot mix asphalt (HMA) have higher mixing, laying and rolling temperatures which leads to higher consumption of fuel. To address this issue, a nano material named ZycoTherm which is chemical warm mix asphalt (WMA) additive with 0.15% by weight of bitumen is added unmodified bitumen (UMB) and Nanosilica modified bitumen (NSMB). This research work is conducted on nanosilica and ZycoTherm modified bitumen to study the physical and mechanical properties of binders and asphalt mixes. The effects of nanosilica and ZycoTherm on physical properties of the binder that is improve softening point, penetration index, viscosity and decrease in penetration value and ductility value of bitumen and also reduce the aging and temperature susceptibility. NSMB results in the increase in stability compared to UMB. WMA modified mix shows slightly higher stability than UMB and NSMB in a lower bitumen content. Using Marshall Mix Design Method selected best trial mixes are NSMB-3% and NSWMA-3%.The optimum bitumen content of NSMB-3% and NSWMA-3% are found to be 4.50% and 4.40% whereas stability 17.30kN and 17.45kN respectively. Tensile strength ratio (TSR) is more than 80%, loss in mass is less than 1% and retained stability is more than 75% for both these mix. NSMB-3% and NSWMA-3% have more resistant to temperature susceptibility, and moisture susceptibility compared to UMB, WMA and other NSMB and NSWMA trial mixes.